Intraband nonresonant optical polaron in semimagnetic semiconductors - Seyid-Rzayeva, S. (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2010)
The theory of a weakly-coupling optical polaron for a narrow gap semimagnetic semiconductor with anisotropic energy spectrum is developed in an external magnetic field. The socalled intraband nonresonant polaron in a classical magnetic field is considered. Analytical expressions for main characteristic of the polaron, such as binding energy and lowest polaron subband energy, transverse and longitudinal polaron effective masses of the electron, are also found. The threshold mechanism for existence of intraband nonresonant polaron in a classical magnetic field is discovered. In the case of intraband polaron the general conditions for the determination of permissible magnetic field regions are established at given low temperature. The